2023
DOI: 10.31083/j.fbl2803045
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Inhibits NLRP3 Inflammasome-Mediated Pyroptosis via Activation of Nrf-2/HO-1 Signaling Pathway and Protects against Doxorubicin-Induced Cardiac Dysfunction

Abstract: Background: Doxorubicin (DOX) is an effective broad-spectrum antitumor drug, but its clinical application is limited due to the side effects of cardiac damage. Astragaloside IV (AS-IV) is a significant active component of Astragalus membranaceus that exerts cardioprotective effects through various pathways. However, whether AS-IV exerts protective effects against DOX-induced myocardial injury by regulating the pyroptosis is still unknown and is investigated in this study. Methods: The myocardial injury model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…And it has been shown that GAS5 is involved in renal tubular cell pyroptosis 33 , ovarian cancer 34 and diabetic cardiomyopathy (DCM) 35 induced by NLRP3 inflammasome activation. Previous studies have shown that pyroptosis activation is associated with Cardiac Dysfunction 36 . In the current study, we tested the expression of NLRP3, Caspase-1, IL-1β and GSDMD which are pyroptosis markers.…”
Section: Discussionmentioning
confidence: 97%
“…And it has been shown that GAS5 is involved in renal tubular cell pyroptosis 33 , ovarian cancer 34 and diabetic cardiomyopathy (DCM) 35 induced by NLRP3 inflammasome activation. Previous studies have shown that pyroptosis activation is associated with Cardiac Dysfunction 36 . In the current study, we tested the expression of NLRP3, Caspase-1, IL-1β and GSDMD which are pyroptosis markers.…”
Section: Discussionmentioning
confidence: 97%
“…28 While the occurrence of inflammasome-mediated pyroptosis has been observed in various tissues and cell types, additional evidence is necessary to establish its definitive role in the progression and underlying mechanisms of certain heart diseases. 29 Epidemiological studies have highlighted obesity, hypertension, and aging as key risk factors for HF, thus intensifying research efforts to investigate the crucial pathological involvement of inflammasome and pyroptosis in the pathogenesis of HF. 30 Pyroptosis, a novel form of programmed cell death, has garnered attention in recent years due to its close association with the progression of inflammasome-related heart failure (HF).…”
Section: Discussionmentioning
confidence: 99%
“…The main link between Nrf2 and NLRP3 are intracellular ROS, that could come from both mitochondrial ROS and NOX activation, and can activate both proteins; however, its actions are opposite. In fact, it has been demonstrated that Nrf2 activation before NLRP3 inflammasome activation reduces inflammation in various in vitro and in vivo models of central and peripheral inflammation [ 33 , 34 , 35 , 36 ]. Consistent with all these studies, we have shown that 24 h treatment with tBHQ prior to NLRP3 inflammasome activation reduces NLRP3 inflammasome components both in WT and NOX4 KO mice ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%